1970
DOI: 10.3126/kuset.v8i1.6047
|View full text |Cite
|
Sign up to set email alerts
|

Sediment Impact On Turbine Material: Case Study Of Modi River, Nepal

Abstract: Hydropower is considered as one of the most economical and stable base energy source compared with other sources of energy of Nepal. Researches coherent to this field are not new but yet it is not sufficient, lots of tiles have to be kept for better understanding of hydropower effecting elements. Sand is the most affecting element that damages the turbine blades, so research on relation of sand and turbine is most. This research is done to find out the impact of sediment on turbine material. Modi River sedimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The underwater components such as guide vanes, runner, facing plate and wearing ring are most affected in run off river projects causing forced outage. 5 Studies have shown that up to 80% of hydro turbines required for future installations under Himalayan basin in Nepal will need Francis type of turbine. 6 Most of Francis turbine installed in Nepalese hydropower stations need frequent overhauling for maintenance and repair of eroded parts.…”
Section: Introductionmentioning
confidence: 99%
“…The underwater components such as guide vanes, runner, facing plate and wearing ring are most affected in run off river projects causing forced outage. 5 Studies have shown that up to 80% of hydro turbines required for future installations under Himalayan basin in Nepal will need Francis type of turbine. 6 Most of Francis turbine installed in Nepalese hydropower stations need frequent overhauling for maintenance and repair of eroded parts.…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that the shape of runner blade has a significant effect on velocity distribution and hence on the sediment erosion of the runner. Poudel et al [5] studied the impact of sediment on turbine material. They used a rotating disc apparatus to find out the total impact of sand on turbine material.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have also been carried out to investigate the effect of size and concentration of silt particles on Pelton turbine buckets through laboratory experiments [8,9]. Some of the earlier researches were focused on the impact of sediment particles on turbine materials [11][12][13][14][15][16][17], and to identify coating materials to protect the surface of the turbine components exposed to sediments [11][12][13][14]. Researches have also been carried out for complete mechanical design of turbines by selection of different erosion resistant materials and coatings [18,19].…”
Section: Current Status Of Researchmentioning
confidence: 99%